ANALYSIS OF FACTORS-FACTORS FECTING THE PERFORMANCE OF ACCOUNTING INFORMATION SYSTEMS IN. BPR SHINTA PUTRA PENGASIH KULON PROG - Fauzi Kurniawan; Moch Imron (Jurnal REKSA: Rekayasa Keuangan, Syariah dan Audit, 2014)
This study aims to examine the influence of user participation, user personal techniques, training and education as well as management support on the performance of accounting information systems at PT. BPR Shinta Putra Pengasih. The samples in this study were all employees of PT. BPR Shinta Putra Pengasih working section of marketing, human resources, planning, administration and reporting, and the public. The sample selection was based on purposive sampling by distributing questionnaires. The analysis model used is multiple linear regression. The results show that management support and training and education programs for employees does not affect the performance of accounting information systems, in this case can be seen at a significance level above 0.05 is equal to 0.407 and 0.126. While the personal techniques and user participation affect the performance of accounting information systems, it can be seen from the significant value for the variable and value engineering 0,045 personal significance for variable user participation 0.016. That means the value of the personal significance of variables technique and user participation below 0.05. So the higher the personal techniques and user participation, then the information system performance will increase.